2018
DOI: 10.5606/ehc.2018.005
|View full text |Cite
|
Sign up to set email alerts
|

Are orthobiologics the next chapter in clinical orthopedics? A literature review

Abstract: Orthobiologics are biologically derived materials which aim to promote healing and regeneration of tissues that are the focus of orthopedic surgery. Since bones, ligaments, tendons, and cartilage have different healing and regeneration characteristics, treatment strategies and clinical problems related to these tissues greatly differ. Although orthobiolgics are an old concept, most of the advancements in this field have been accomplished within the last two decades. A large number of promising laboratory studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
28
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 53 publications
0
28
0
Order By: Relevance
“…[6] Although positive results are being reported in the pre-clinical setup, more clinical data are required in order to make a conclusion on this new concept. [7] The addition of PRP to a poly lactic-co-glycolic acid (PLGA) scaffold with continuous passive motion in osteochondral defects may be beneficial for hyaline cartilage and subchondral bone tissue repair. However, PRP alone (with or without PLGA implants) is limited to osteochondral defect repair without significant regeneration.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[6] Although positive results are being reported in the pre-clinical setup, more clinical data are required in order to make a conclusion on this new concept. [7] The addition of PRP to a poly lactic-co-glycolic acid (PLGA) scaffold with continuous passive motion in osteochondral defects may be beneficial for hyaline cartilage and subchondral bone tissue repair. However, PRP alone (with or without PLGA implants) is limited to osteochondral defect repair without significant regeneration.…”
mentioning
confidence: 99%
“…[12] Finally, current clinical experience on orthobiologics should be regarded as first steps for the new concept of musculoskeletal system healing and is still in experimental stage. [7] No definitive conclusions can be established about the effects of PRP in such conditions since most studies are of low to moderate methodological quality and use variable PRP protocols. For these reasons, there is a growing debate regarding PRP's clinical efficacy.…”
mentioning
confidence: 99%
“…Therefore, our study is different from these studies as it shows individual activity of PDGF in a collagen sponge scaffold. [17] In a clinical study, the PDGF concentration was significantly higher in anterior cruciate ligament reconstructed knee group than in the meniscectomy group and correlated with a higher healing rate of the meniscus. Therefore, it has been suggested that PDGF may have a critical role in the healing response of meniscus suture.…”
Section: Discussionmentioning
confidence: 91%
“…[2,3] Rupture of the Achilles tendon can be treated through conservative methods. [4] One of the most controversial topics on tendon healing is undoubtedly related to Achilles tendon rupture. [4] In a recent study, it was detected that locally administered tranexamic acid has an adverse effect on tendon healing in late period.…”
mentioning
confidence: 99%
“…[4] One of the most controversial topics on tendon healing is undoubtedly related to Achilles tendon rupture. [4] In a recent study, it was detected that locally administered tranexamic acid has an adverse effect on tendon healing in late period. [5] Eren et al [6] reported that histopathological examination revealed that both low molecular weight heparin and rivaroxaban have positive effects on tendon healing.…”
mentioning
confidence: 99%